Management of acute diarrhea in children by community pharmacists in Lagos, Nigeria - Ogbo PU; Aina BA; Aderemi-Williams RI (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Background: Acute diarrhea in children leads to dehydration and death if not appropriately managed. World Health Organization (WHO) recommends treating diarrhea with oral rehydration therapy (ORT), fluids and foods. Proper management is hinged on accurate assessment of patients to identify the acute watery diarrhea. Objective: To compare the knowledge and attitude of community pharmacists in the management of acute diarrhea in children with their observed practice. Methods: This study was carried out using two instruments: structured self-administered questionnaire to assess knowledge and attitude of community pharmacists in the management of acute diarrhea in children and simulated patient visits to evaluate assessment of patients, recommendation of products and instructions on feeding and fluid intake. The simulated patient visits were done in 186 pharmacies in the city of Lagos, Nigeria. Results: The study reveals that the knowledge and attitude of community pharmacists in the management of acute diarrhea in children was different from their observed practice. The difference was statistically significant (p<0.05). During the simulations, 23% carried out appropriate assessment before recommending any products, and 15% recommended ORT alone. Although information to the pharmacists indicated non-dysentery, non-cholera, acute watery diarrhea, antibiotics and antidiarrheals were irrationally recommended and these were the mainstay of symptoms' management in practice. Questionnaire data revealed that 24% of pharmacists knew the correct instructions to give on food and fluid intake during diarrhea, whereas 8% followed WHO guideline on food and fluid intake during the visits. Conclusions: Assessment of patients to determine acute diarrhea was inadequate. Observed practice in managing acute diarrhea in children was inappropriate and significantly different from their claims in the questionnaire. The recommendation of ORT was scanty and advice on food and fluid intake was inadequate and sometimes inappropriate. This study shows that only 15% of community pharmacists managed acute diarrhea in children according to the WHO guidelines.